Utility of IL-6 in the Diagnosis, Treatment and Prognosis of COVID-19 Patients: A Longitudinal Study - Vikram Jain; Pratap Kumar; Prasan Kumar Panda; Mohan Suresh; Karanvir Kaushal; Anissa A. Mirza; Rohit Raina; Sarama Saha; Balram J. Omar; Vivekanandhan Subbiah (Vaccines, 2022)
COVID-19 has caused devastating effects worldwide ever since its origin in December 2019. IL-6 is one of the chief markers used in the management of COVID-19. We conducted a longitudinal study to investigate the role of IL-6 in diagnosis, treatment, and prognosis of COVID-19-related cytokine storm. Patients with COVID-19 who were admitted at AIIMS Rishikesh from March to December 2020 were included in the study. Patients with no baseline IL-6 value at admission and for whom clinical data were not available were excluded. Clinical and laboratory data of these patients were collected from the e-hospital portal and entered in an excel sheet. Correlation was seen with other inflammatory markers and outcomes were assessed using MS Excel 2010 and SPSS software. A total of 131 patients were included in the study. Of these, 74.8% were males, with mean age 55.03 ± 13.57 years, and mean duration from symptom onset being 6.69 ± 6.3 days. A total of 82.4% had WHO severe category COVID-19, with 46.56% having severe hypoxia at presentation and 61.8% of them having some comorbidity. Spearman rank correlation coefficient of IL-6 with D-dimer was 0.203, with LDH was −0.005, with ferritin was 0.3, and with uric acid was 0.123. A total of 11 patients received Tocilizumab at a mean duration from symptom onset of 18.09 days, and 100% mortality was observed. Deaths were reported more in the group with IL-6 ≥ 40 pg/mL (57.1% vs. 40.2%, p = 0.06). ICU admissions and ventilator requirement were higher in the IL-6 ≥ 40 pg/mL group (95.9% vs. 91.4%, p = 0.32 and 55.1% vs. 37.8%, p = 0.05). The study showed that IL-6 can be used as a possible “thrombotic cytokine marker”. Higher values of IL-6 (≥40 pg/mL) are associated with more deaths, ICU admissions, and ventilator requirement.